Mesoporous carbon nitride used as negative electrode material for lithium ion battery and preparation method thereof
By using mesoporous carbon nitride as the negative electrode material in lithium-ion batteries, the problem of insufficient battery electrochemical performance in the existing technology is solved, and the effects of simplifying the process flow, reducing costs, and improving battery performance are achieved.
Patent Information
- Application Number
- CN202211313520.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-25
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2042-10-25
AI Technical Summary
The prior art is difficult to provide a carbon nitride suitable for use as the negative electrode material of lithium-ion batteries, and its preparation method is complex and costly, making it difficult to improve the electrochemical performance of the battery.
By mixing carbonitride, chloride and water, performing freeze-drying and high-temperature treatment, mesoporous carbon nitride with a porous structure is finally obtained, which can be used as anode material for lithium-ion batteries. This method includes multiple heating stages of high-temperature treatment and pickling to ensure the uniformity and purity of the pore structure.
The electrochemical performance of lithium-ion batteries is significantly improved, the process flow is simplified, the preparation cost is reduced, and the economic benefits are improved. The porous structure of mesoporous carbon nitride and abundant defective pyridine N and pyrrole N vacancies provide more Li adsorption sites and improve the charge and discharge performance of the battery.
Smart Images

Figure CN115626611B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of lithium ion batteries and relates to a negative electrode material, in particular to a mesoporous carbon nitride used as a negative electrode material for lithium ion batteries and a preparation method thereof. Background Art
[0002] As a product of the 1980s, lithium-ion batteries have been successfully commercialized in many fields after decades of rapid development due to their many performance and technological advantages. According to the differences in usage scenarios and energy sizes, lithium-ion batteries can be specifically divided into lithium power batteries, lithium consumer batteries and lithium energy storage batteries. For each of the above lithium-ion batteries, the negative electrode material is a crucial component, whether from the perspective of energy density, service life, preparation cost, or safety performance.
[0003] Early lithium-ion batteries mainly used metallic lithium as the negative electrode material, but lithium dendrites inevitably appeared during multiple charge and discharge cycles, which could easily puncture the battery separator and cause a short circuit, thus causing safety accidents. Therefore, metallic lithium has been gradually abandoned as a negative electrode material. Currently, the negative electrode materials of lithium-ion batteries in large-scale commercialization are mainly graphite carbon materials and lithium titanate. Other negative electrode materials that are still in the research stage mainly include transition metal oxides, silicon-based materials and other carbon materials.
[0004] In recent years, graphite carbon nitride has gradually attracted extensive attention in research and application due to its unique structure and excellent performance. Its potential value in the fields of energy, catalysis, and sensing has been continuously developed, and important results have been achieved in the fields of chemistry, materials, physics, biology, environment, and energy. Therefore, using it as a negative electrode material for lithium-ion batteries has become a bold attempt for those skilled in the art.
[0005] CN 105152147A discloses a method for preparing a water-soluble luminescent graphite phase carbon nitride nano-kelp, wherein nitrogen- and carbon-containing precursors are subjected to high-temperature polycondensation in a mixed chloride molten salt system to obtain a water-soluble luminescent graphite phase carbon nitride nano-kelp. The preparation method can obtain the target product using different types of precursors, and the prepared nano-kelp has a uniform shape, good dispersibility in water, can form a high-concentration stable transparent colloidal solution, and can stably exist in both alkaline and weakly acidic environments. Under the excitation of ultraviolet light, the nano-kelp solid and its colloidal solution have strong blue photoluminescence and stable luminescence. However, due to its good photoluminescence performance and water solubility, the nano-kelp is only suitable for fluorescent probes, biological imaging, biomedical engineering, analytical monitoring and other fields, and is not suitable for negative electrode materials of lithium-ion batteries.
[0006] CN 112142023A discloses a method for preparing ionized carbon nitride, which specifically comprises: dissolving urea in water, then adding a mixture of sodium chloride and potassium chloride to fully dissolve the urea, and obtaining ionized carbon nitride under the condition of rapid heating of the solution; and obtaining an aqueous solution of ionized carbon nitride by dialysis, filtration or centrifugation; and drying to obtain a powder of ionized carbon nitride. Although the ionized carbon nitride can be applied to the fields of photoelectrocatalysis, chemical sensing, photoelectric devices, etc. due to its excellent photocatalytic performance, it is also not suitable for negative electrode materials of lithium ion batteries.
[0007] It can be seen that how to provide a carbon nitride used as a negative electrode material for lithium-ion batteries and a preparation method thereof to improve the electrochemical performance of the battery while simplifying the process flow and reducing the preparation cost has become an urgent problem that technical personnel in this field need to solve. Summary of the invention
[0008] The object of the present invention is to provide a mesoporous carbon nitride used as a negative electrode material for a lithium ion battery and a preparation method thereof. The mesoporous carbon nitride used as a negative electrode material for a lithium ion battery can significantly improve the electrochemical performance of the battery, and the preparation method has a simple process, reduces the preparation cost, and improves the economic benefit.
[0009] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0010] In a first aspect, the present invention provides a method for preparing mesoporous carbon nitride used as a negative electrode material for a lithium ion battery, the preparation method comprising the following steps:
[0011] (1) mixing carbon and nitrogen compounds, chlorides and water, and fully dissolving them to obtain a precursor solution;
[0012] (2) freeze-drying the precursor solution obtained in step (1) to obtain a precursor powder;
[0013] (3) subjecting the precursor powder obtained in step (2) to a high temperature treatment in at least two heating stages to obtain a crude carbon nitride product;
[0014] (4) The crude carbon nitride obtained in step (3) is sequentially acid-washed, water-washed and dried to obtain mesoporous carbon nitride.
[0015] The preparation method provided by the present invention comprises dissolution, freeze drying, high temperature treatment and post-treatment processes in sequence, and finally obtains mesoporous carbon nitride suitable for negative electrode materials of lithium ion batteries. The whole preparation process is simple, the reaction is green and pollution-free, the operating conditions are easy to control, the preparation cost is reduced, and the economic benefit is improved.
[0016] In the present invention, the freeze-drying treatment promotes the full mixing of chloride as a template in the carbon-nitrogen compound, thereby achieving a uniform distribution of the internal pore structure of the obtained carbon nitride; the high-temperature treatment is divided into at least two heating stages, which ensures the full development of the pore structure and avoids the collapse of the pores caused by too fast heating, further improving the uniformity of the pore distribution; the acid washing removes the chloride microcrystals doped in the crude carbon nitride, and the purity of the mesoporous carbon nitride is further improved through subsequent water washing.
[0017] Compared with common graphite materials, the mesoporous carbon nitride obtained in the present invention has a larger specific surface area due to its porous structure, thereby providing more adsorption sites; at the same time, the mesoporous carbon nitride has abundant defective pyridinic N and pyrrolic N vacant sites, which can provide additional Li adsorption sites, and the defective pyridinic N has stronger electronegativity and can more easily adsorb Li, thereby significantly improving the electrochemical performance of lithium-ion batteries when it is used as a negative electrode material.
[0018] Preferably, the carbon-nitrogen compound in step (1) comprises any one of urea, dicyandiamide or melamine, or a combination of at least two thereof. Typical but non-limiting combinations include a combination of urea and dicyandiamide, a combination of dicyandiamide and melamine, a combination of urea and melamine, or a combination of urea, dicyandiamide and melamine, and urea is further preferred.
[0019] Preferably, the chloride in step (1) comprises potassium chloride and / or sodium chloride, more preferably potassium chloride.
[0020] Preferably, the mixing mass ratio of the carbon nitrogen compound and the chloride in step (1) is (5-15):1, for example, it can be 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1 or 15:1, and is further preferably (8-12):1, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0021] In the present invention, the mixing mass ratio of the carbonitride and the chloride is crucial for the formation and distribution of the pore structure of carbon nitride. When the mixing mass ratio is lower than 5:1, that is, there is too much chloride as a template, resulting in the carbon nitride being mainly macropores, the specific surface area being reduced, and the pore collapse phenomenon being prone to occur; when the mixing mass ratio is higher than 15:1, that is, there is too little chloride as a template, resulting in the carbon nitride being mainly micropores, or even having no pore structure, which will also reduce the specific surface area and thus reduce the number of adsorption sites.
[0022] Preferably, the dissolution process in step (1) is accompanied by stirring, and the stirring rate is 100-1000 rpm, for example, it can be 100 rpm, 200 rpm, 300 rpm, 400 rpm, 500 rpm, 600 rpm, 700 rpm, 800 rpm, 900 rpm or 1000 rpm, but is not limited to the listed values, and other values not listed within the numerical range are also applicable.
[0023] Preferably, the freeze-drying process in step (2) comprises low-temperature freezing and vacuum sublimation performed sequentially.
[0024] Preferably, the low-temperature freezing temperature is -10 to -50°C, for example, it can be -10°C, -15°C, -20°C, -25°C, -30°C, -35°C, -40°C, -45°C or -50°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0025] Preferably, the absolute gas pressure of the vacuum sublimation is 1-10Pa, for example, it can be 1Pa, 2Pa, 3Pa, 4Pa, 5Pa, 6Pa, 7Pa, 8Pa, 9Pa or 10Pa, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0026] Preferably, the high temperature treatment in step (3) includes two heating stages, namely a first heating stage and a second heating stage.
[0027] Preferably, the heating rate in the first heating stage is 4-6°C / min, for example, it can be 4°C / min, 4.2°C / min, 4.4°C / min, 4.6°C / min, 4.8°C / min, 5°C / min, 5.2°C / min, 5.4°C / min, 5.6°C / min, 5.8°C / min or 6°C / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0028] Preferably, the target temperature of the first heating stage is 300-400°C, for example, it can be 300°C, 310°C, 320°C, 330°C, 340°C, 350°C, 360°C, 370°C, 380°C, 390°C or 400°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0029] Preferably, the insulation time of the first heating stage is 2-4h, for example, it can be 2h, 2.2h, 2.4h, 2.6h, 2.8h, 3h, 3.2h, 3.4h, 3.6h, 3.8h or 4h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0030] Preferably, the heating rate of the second heating stage is 1-3°C / min, for example, it can be 1°C / min, 1.2°C / min, 1.4°C / min, 1.6°C / min, 1.8°C / min, 2°C / min, 2.2°C / min, 2.4°C / min, 2.6°C / min, 2.8°C / min or 3°C / min, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0031] Preferably, the target temperature of the second heating stage is 600-650°C, for example, it can be 600°C, 605°C, 610°C, 615°C, 620°C, 625°C, 630°C, 635°C, 640°C, 645°C or 650°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0032] Preferably, the insulation time of the second heating stage is 3-5h, for example, it can be 3h, 3.2h, 3.4h, 3.6h, 3.8h, 4h, 4.2h, 4.4h, 4.6h, 4.8h or 5h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0033] Preferably, the acid solution used for pickling in step (4) includes any one of hydrochloric acid solution, nitric acid solution or sulfuric acid solution, and is more preferably hydrochloric acid solution.
[0034] Preferably, the acid concentration used in the pickling in step (4) is 0.08-0.12 mol / L, for example, it can be 0.08 mol / L, 0.09 mol / L, 0.1 mol / L, 0.1 mol / L, 0.11 mol / L or 0.12 mol / L, but it is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0035] Preferably, the washing in step (4) is carried out using deionized water.
[0036] Preferably, the water washing in step (4) is carried out until the washing liquid becomes neutral.
[0037] Preferably, the drying temperature in step (4) is 80-120°C, for example, it can be 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, 110°C, 115°C or 120°C, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0038] Preferably, the drying time in step (4) is 4-6 h, for example, 4 h, 4.2 h, 4.4 h, 4.6 h, 4.8 h, 5 h, 5.2 h, 5.4 h, 5.6 h, 5.8 h or 6 h, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0039] As a preferred technical solution of the first aspect of the present invention, the preparation method comprises the following steps:
[0040] (1) mixing urea, potassium chloride and water, wherein the mass ratio of urea to potassium chloride is (8-12):1, and stirring at a rate of 100-1000 rpm until the urea is fully dissolved to obtain a precursor solution;
[0041] (2) freeze-drying the precursor solution obtained in step (1) to obtain a precursor powder; the freeze-drying process includes low-temperature freezing and vacuum sublimation performed in sequence, and the low-temperature freezing temperature is -10 to -50°C, and the absolute pressure of the vacuum sublimation is 1-10Pa;
[0042] (3) subjecting the precursor powder obtained in step (2) to high temperature treatment to obtain a crude carbon nitride product; the high temperature treatment comprises two heating stages, namely a first heating stage and a second heating stage; the heating rate of the first heating stage is 4-6°C / min, the target temperature is 300-400°C, and the holding time is 2-4h; the heating rate of the second heating stage is 1-3°C / min, the target temperature is 600-650°C, and the holding time is 3-5h;
[0043] (4) The crude carbon nitride obtained in step (3) is acid-washed, water-washed and dried in sequence to obtain mesoporous carbon nitride; the acid-washing is performed using a hydrochloric acid solution with a concentration of 0.08-0.12 mol / L; the water-washing is performed using deionized water until the washing solution is neutral; the drying temperature is 80-120° C. and the drying time is 4-6 h.
[0044] In a second aspect, the present invention provides a mesoporous carbon nitride used as a negative electrode material for a lithium ion battery obtained by the preparation method described in the first aspect, wherein the average pore size of the mesoporous carbon nitride is 3-6nm, for example, it can be 3nm, 3.5nm, 4nm, 4.5nm, 5nm, 5.5nm or 6nm, but is not limited to the listed values, and other unlisted values within the numerical range are also applicable.
[0045] Compared with the prior art, the present invention has the following beneficial effects:
[0046] (1) The preparation method provided by the present invention sequentially performs dissolution, freeze drying, high temperature treatment and post-treatment processes to finally prepare mesoporous carbon nitride suitable for negative electrode materials of lithium ion batteries. The whole preparation process is simple, the reaction is green and pollution-free, the operating conditions are easy to control, the preparation cost is reduced, and the economic benefits are improved;
[0047] (2) The present invention promotes the full mixing of chloride, a template, in carbon and nitrogen compounds through freeze-drying treatment, thereby achieving uniform distribution of the internal pore structure of the obtained carbon nitride; the high temperature treatment is divided into at least two heating stages, which ensures the full development of the pore structure and avoids the collapse of the pores caused by too fast heating, further improving the uniformity of the pore distribution; the acid washing removes the chloride microcrystals doped in the crude carbon nitride, and the purity of the mesoporous carbon nitride is further improved through subsequent water washing;
[0048] (3) Compared with ordinary graphite materials, the mesoporous carbon nitride obtained in the present invention has a larger specific surface area due to its porous structure, thereby providing more adsorption sites; at the same time, the mesoporous carbon nitride has abundant defective pyridinic N and pyrrolic N vacant sites, which can provide additional Li adsorption sites, and the defective pyridinic N has stronger electronegativity and can more easily adsorb Li, thereby significantly improving the electrochemical performance of lithium-ion batteries when it is used as a negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0049] Figure 1 1 is a lithium ion battery performance test curve corresponding to the carbon nitride obtained in Example 1 and Comparative Examples 1-3;
[0050] Figure 2 It is the lithium ion battery cycle performance curve corresponding to the carbon nitride obtained in Example 1 and Comparative Examples 1-3. DETAILED DESCRIPTION
[0051] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0052] Example 1
[0053] This embodiment provides a mesoporous carbon nitride used as a negative electrode material for a lithium ion battery and a preparation method thereof, the preparation method comprising the following steps:
[0054] (1) mixing urea, potassium chloride and water in a mass ratio of 10:1, and stirring at a rate of 500 rpm until the urea is fully dissolved to obtain a precursor solution;
[0055] (2) freeze-drying the precursor solution obtained in step (1) to obtain a precursor powder; the freeze-drying process includes low-temperature freezing and vacuum sublimation performed in sequence, and the low-temperature freezing temperature is -30°C, and the absolute pressure of the vacuum sublimation is 5 Pa;
[0056] (3) subjecting the precursor powder obtained in step (2) to high temperature treatment to obtain a crude carbon nitride product; the high temperature treatment comprises two heating stages, namely a first heating stage and a second heating stage; the heating rate of the first heating stage is 5°C / min, the target temperature is 350°C, and the holding time is 3h; the heating rate of the second heating stage is 2°C / min, the target temperature is 620°C, and the holding time is 4h;
[0057] (4) The crude carbon nitride obtained in step (3) is sequentially acid-washed, water-washed and dried to obtain mesoporous carbon nitride; the acid-washing is performed using a hydrochloric acid solution with a concentration of 0.1 mol / L; the water-washing is performed using deionized water until the washing solution is neutral; the drying temperature is 100° C. and the drying time is 5 h.
[0058] Example 2
[0059] This embodiment provides a mesoporous carbon nitride used as a negative electrode material for a lithium ion battery and a preparation method thereof, the preparation method comprising the following steps:
[0060] (1) mixing urea, potassium chloride and water in a mass ratio of 8:1, and stirring at a rate of 200 rpm until the urea is fully dissolved to obtain a precursor solution;
[0061] (2) freeze-drying the precursor solution obtained in step (1) to obtain a precursor powder; the freeze-drying process includes low-temperature freezing and vacuum sublimation performed in sequence, and the temperature of the low-temperature freezing is -20°C, and the absolute pressure of the vacuum sublimation is 8 Pa;
[0062] (3) subjecting the precursor powder obtained in step (2) to high temperature treatment to obtain a crude carbon nitride product; the high temperature treatment comprises two heating stages, namely a first heating stage and a second heating stage; the heating rate of the first heating stage is 5°C / min, the target temperature is 350°C, and the holding time is 3h; the heating rate of the second heating stage is 2°C / min, the target temperature is 620°C, and the holding time is 4h;
[0063] (4) The crude carbon nitride obtained in step (3) is sequentially acid-washed, water-washed and dried to obtain mesoporous carbon nitride; the acid-washing is performed using a hydrochloric acid solution with a concentration of 0.09 mol / L; the water-washing is performed using deionized water until the washing solution is neutral; the drying temperature is 90° C. and the drying time is 5 h.
[0064] Example 3
[0065] This embodiment provides a mesoporous carbon nitride used as a negative electrode material for a lithium ion battery and a preparation method thereof, the preparation method comprising the following steps:
[0066] (1) mixing urea, potassium chloride and water in a mass ratio of 12:1, and stirring at a rate of 800 rpm until the urea is fully dissolved to obtain a precursor solution;
[0067] (2) freeze-drying the precursor solution obtained in step (1) to obtain a precursor powder; the freeze-drying process includes low-temperature freezing and vacuum sublimation performed in sequence, and the temperature of the low-temperature freezing is -40°C, and the absolute pressure of the vacuum sublimation is 3 Pa;
[0068] (3) subjecting the precursor powder obtained in step (2) to high temperature treatment to obtain a crude carbon nitride product; the high temperature treatment comprises two heating stages, namely a first heating stage and a second heating stage; the heating rate of the first heating stage is 5°C / min, the target temperature is 350°C, and the holding time is 3h; the heating rate of the second heating stage is 2°C / min, the target temperature is 620°C, and the holding time is 4h;
[0069] (4) The crude carbon nitride obtained in step (3) is sequentially acid-washed, water-washed and dried to obtain mesoporous carbon nitride; the acid-washing is performed using a hydrochloric acid solution with a concentration of 0.11 mol / L; the water-washing is performed using deionized water until the washing solution is neutral; the drying temperature is 110° C. and the drying time is 5 h.
[0070] Example 4
[0071] This embodiment provides a mesoporous carbon nitride used as a negative electrode material for a lithium ion battery and a preparation method thereof, the preparation method comprising the following steps:
[0072] (1) mixing urea, potassium chloride and water in a mass ratio of 5:1, and stirring at a rate of 100 rpm until the urea is fully dissolved to obtain a precursor solution;
[0073] (2) freeze-drying the precursor solution obtained in step (1) to obtain a precursor powder; the freeze-drying process includes low-temperature freezing and vacuum sublimation performed in sequence, and the temperature of the low-temperature freezing is -10°C, and the absolute pressure of the vacuum sublimation is 10Pa;
[0074] (3) subjecting the precursor powder obtained in step (2) to high temperature treatment to obtain a crude carbon nitride product; the high temperature treatment includes two heating stages, namely a first heating stage and a second heating stage; the heating rate of the first heating stage is 4°C / min, the target temperature is 300°C, and the holding time is 4h; the heating rate of the second heating stage is 1°C / min, the target temperature is 600°C, and the holding time is 5h;
[0075] (4) The crude carbon nitride obtained in step (3) is sequentially acid-washed, water-washed and dried to obtain mesoporous carbon nitride; the acid-washing is performed using a hydrochloric acid solution with a concentration of 0.08 mol / L; the water-washing is performed using deionized water until the washing solution is neutral; the drying temperature is 80° C. and the drying time is 6 h.
[0076] Example 5
[0077] This embodiment provides a mesoporous carbon nitride used as a negative electrode material for a lithium ion battery and a preparation method thereof, the preparation method comprising the following steps:
[0078] (1) mixing urea, potassium chloride and water in a mass ratio of urea to potassium chloride of 15:1, and stirring at a rate of 1000 rpm until the mixture is fully dissolved to obtain a precursor solution;
[0079] (2) freeze-drying the precursor solution obtained in step (1) to obtain a precursor powder; the freeze-drying process includes low-temperature freezing and vacuum sublimation performed in sequence, and the temperature of the low-temperature freezing is -50°C, and the absolute pressure of the vacuum sublimation is 1 Pa;
[0080] (3) subjecting the precursor powder obtained in step (2) to high temperature treatment to obtain a crude carbon nitride product; the high temperature treatment comprises two heating stages, namely a first heating stage and a second heating stage; the heating rate of the first heating stage is 6°C / min, the target temperature is 400°C, and the holding time is 2h; the heating rate of the second heating stage is 3°C / min, the target temperature is 650°C, and the holding time is 3h;
[0081] (4) The crude carbon nitride obtained in step (3) is sequentially acid-washed, water-washed and dried to obtain mesoporous carbon nitride; the acid-washing is performed using a hydrochloric acid solution with a concentration of 0.12 mol / L; the water-washing is performed using deionized water until the washing solution is neutral; the drying temperature is 120° C. and the drying time is 4 h.
[0082] Example 6
[0083] The present embodiment provides a mesoporous carbon nitride used as a negative electrode material for a lithium ion battery and a preparation method thereof. In the preparation method, except that the urea in step (1) is replaced by dicyandiamide, the remaining steps and conditions are the same as those in Example 1, and thus are not described in detail here.
[0084] Example 7
[0085] This embodiment provides a mesoporous carbon nitride used as a negative electrode material for a lithium ion battery and a preparation method thereof. In the preparation method, except that the urea in step (1) is replaced by melamine, the remaining steps and conditions are the same as those in Example 1, and therefore are not described in detail here.
[0086] Example 8
[0087] The present embodiment provides a mesoporous carbon nitride used as a negative electrode material for a lithium ion battery and a preparation method thereof. In the preparation method, except that the urea in step (1) is replaced with urea and dicyandiamide mixed in equal masses, the remaining steps and conditions are the same as those in Example 1, and therefore are not described in detail here.
[0088] Example 9
[0089] This embodiment provides a mesoporous carbon nitride used as a negative electrode material for a lithium ion battery and a preparation method thereof. In the preparation method, except that the potassium chloride in step (1) is replaced by sodium chloride, the remaining steps and conditions are the same as those in Example 1, and thus are not described in detail here.
[0090] Example 10
[0091] The present embodiment provides a mesoporous carbon nitride used as a negative electrode material for a lithium ion battery and a preparation method thereof. In the preparation method, except that the potassium chloride in step (1) is replaced by potassium chloride and sodium chloride mixed in equal masses, the remaining steps and conditions are the same as those in Example 1, and therefore are not described in detail here.
[0092] Embodiment 11
[0093] The present embodiment provides a mesoporous carbon nitride used as a negative electrode material for a lithium ion battery and a preparation method thereof. In the preparation method, except that the mixing mass ratio in step (1) is changed to 2:1, the remaining steps and conditions are the same as those in Example 1, and thus are not described in detail here.
[0094] Example 12
[0095] The present embodiment provides a mesoporous carbon nitride used as a negative electrode material for a lithium ion battery and a preparation method thereof. In the preparation method, except that the mixing mass ratio in step (1) is changed to 18:1, the remaining steps and conditions are the same as those in Example 1, and thus are not described in detail here.
[0096] Comparative Example 1
[0097] This comparative example provides a carbon nitride used as a negative electrode material for a lithium ion battery and a preparation method thereof. In the preparation method, except that the high temperature treatment in step (3) is changed to one heating stage, and the heating rate is 3°C / min, the target temperature is 620°C, and the insulation time is 5h, the remaining steps and conditions are the same as those in Example 1, and therefore are not described here.
[0098] Comparative Example 2
[0099] This comparative example provides a carbon nitride used as a negative electrode material for a lithium ion battery and a preparation method thereof, the preparation method comprising the following steps:
[0100] (1) urea and potassium chloride were mixed in a mass ratio of 10:1, and stirred at a rate of 500 rpm to obtain a precursor powder;
[0101] (2) subjecting the precursor powder obtained in step (1) to high temperature treatment to obtain a crude carbon nitride product; the high temperature treatment comprises two heating stages, namely a first heating stage and a second heating stage; the heating rate of the first heating stage is 5°C / min, the target temperature is 350°C, and the holding time is 3h; the heating rate of the second heating stage is 2°C / min, the target temperature is 620°C, and the holding time is 4h;
[0102] (3) The crude carbon nitride obtained in step (2) is sequentially acid-washed, water-washed and dried to obtain mesoporous carbon nitride; the acid-washing is performed using a hydrochloric acid solution with a concentration of 0.1 mol / L; the water-washing is performed using deionized water until the washing solution is neutral; the drying temperature is 100° C. and the drying time is 5 h.
[0103] Comparative Example 3
[0104] This comparative example provides a carbon nitride used as a negative electrode material for a lithium ion battery and a preparation method thereof, the preparation method comprising the following steps:
[0105] (1) subjecting urea to high temperature treatment to obtain a crude carbon nitride; the high temperature treatment comprises two heating stages, namely a first heating stage and a second heating stage; the heating rate of the first heating stage is 5°C / min, the target temperature is 350°C, and the holding time is 3h; the heating rate of the second heating stage is 2°C / min, the target temperature is 620°C, and the holding time is 4h;
[0106] (2) The crude carbon nitride obtained in step (1) is sequentially acid-washed, water-washed and dried to obtain mesoporous carbon nitride; the acid-washing is performed using a hydrochloric acid solution with a concentration of 0.1 mol / L; the water-washing is performed using deionized water until the washing solution is neutral; the drying temperature is 100° C. and the drying time is 5 h.
[0107] After testing, the pore structure parameters of the carbon nitride obtained in Examples 1-12 and Comparative Examples 1-3 are shown in Table 1 below.
[0108] Table 1
[0109] Carbon Nitride Average pore size (nm) <![CDATA[Specific surface area (m 2 / g)]]> <![CDATA[Pore volume (cm 3 / g)]]> Example 1 4.52 255 0.51 Example 2 4.61 286 0.53 Example 3 4.42 202 0.51 Example 4 4.85 301 0.55 Example 5 4.26 185 0.47 Example 6 4.54 258 0.50 Example 7 4.52 262 052 Example 8 4.58 259 0.52 Example 9 4.55 245 051 Example 10 4.50 254 0.55 Embodiment 11 6.58 310 0.56 Example 12 2.39 170 0.42 Comparative Example 1 5.67 210 0.57 Comparative Example 2 6.82 115 0.41 Comparative Example 3 1.27 95 0.23
[0110] It can be seen from Table 1 that the ratio of urea to potassium chloride needs to be precisely controlled within a reasonable range. When the amount of potassium chloride is relatively small, it is not enough to form a mesoporous structure. When the amount of potassium chloride is relatively large, the pore size tends to become larger. Freeze-drying urea and potassium chloride can help form mesoporous carbon nitride. Setting a temperature gradient can also help generate mesoporous carbon nitride. Some nitrogen-carbon compounds can also be used as precursors to generate carbon nitride. Sodium chloride and potassium chloride can both be used as salt templates.
[0111] The carbon nitride obtained in Example 1 and Comparative Examples 1-3 was used as the negative electrode material to prepare a lithium ion battery. The specific preparation method was as follows: a 2032-type button cell was used for full-battery electrochemical testing, ternary nickel cobalt manganese oxide (NCM613) was used as the positive electrode material, and mesoporous carbon nitride was used as the negative electrode material to assemble a full battery for testing. The nickel cobalt manganese oxide, the binder PVDF and the conductive agent acetylene black were fully stirred and mixed in an appropriate amount of NMP solvent in a mass ratio of 80:10:10, and evenly coated on aluminum foil, and then vacuum dried at 90°C for 8h; after cutting and pressing the positive electrode sheet, weighing and marking, and placing it in a vacuum drying oven at 90°C for about 2h to obtain a positive electrode sheet; the mesoporous carbon nitride was ground and then pressed to obtain a negative electrode sheet; the battery was installed under the condition that the oxygen content and water content were both less than 2.0ppm, and the battery was left to stand for more than 6h for charge and discharge testing.
[0112] The lithium ion battery performance test curves corresponding to the carbon nitride obtained in Example 1 and Comparative Examples 1-3 are shown in Figure 1 , cycle performance curve see Figure 2 .
[0113] Among them, the test conditions of the performance test curve are: the charging and discharging mechanism of the battery test is constant current-constant voltage charging and constant current discharging. The cut-off voltage of constant current charging is 4.25V, and the cut-off current of constant voltage charging is 0.03C; the cut-off voltage of constant current discharging is 2.5V; the battery needs to be activated three times at 0.2C and 0.5C before testing.
[0114] The test conditions of the cycle performance curve are as follows: the charge and discharge cycle test of the electrode material is carried out at a current density of 1C, and the rate performance test is cycled 50 times at a rate of 1C; the room temperature test temperature is 25±3°C, and the high temperature test temperature is 60°C.
[0115] Depend on Figure 1It can be seen that: the charging curves of Example 1 and Comparative Examples 1-3 are almost identical, and the discharge curves are very different; the discharge capacity of Example 1 can reach 166.7 mAh / g, the discharge capacity of Comparative Example 1 is 159.8 mAh / g, the discharge capacity of Comparative Example 2 is 157.6 mAh / g, and the discharge capacity of Comparative Example 3 is 153.3 mAh / g, indicating that the battery performance of Example 1 far exceeds that of Comparative Examples 1-3.
[0116] Depend on Figure 2 It can be seen that: the assembled full battery was subjected to a 1C rate cycle test. After 50 cycles, the capacity retention rate of Example 1 was 99.09%, the capacity retention rate of Comparative Example 1 was 96.54%, the capacity retention rate of Comparative Example 2 was 92.32%, and the capacity retention rate of Comparative Example 3 was 79.47%. The difference is obvious, indicating that the rate cycle performance of Example 1 is much better than that of Comparative Examples 1-3.
[0117] It can be seen that the preparation method provided by the present invention finally obtains mesoporous carbon nitride suitable for lithium-ion battery negative electrode materials by sequentially performing dissolution, freeze-drying, high-temperature treatment and post-treatment processes. The whole preparation process is simple, the reaction is green and pollution-free, the operating conditions are easy to control, the preparation cost is reduced, and the economic benefits are improved.
[0118] Among them, the freeze-drying treatment promotes the full mixing of chloride as a template in the carbon-nitrogen compound, thereby achieving a uniform distribution of the internal pore structure of the obtained carbon nitride; the high-temperature treatment is divided into at least two heating stages, which ensures the full development of the pore structure, while avoiding the collapse of the pores caused by too rapid heating, further improving the uniformity of the pore distribution; the acid pickling removes the chloride microcrystals doped in the crude carbon nitride, and the subsequent water washing further improves the purity of the mesoporous carbon nitride.
[0119] In addition, compared with ordinary graphite materials, the mesoporous carbon nitride obtained in the present invention has a larger specific surface area due to its porous structure, thereby providing more adsorption sites; at the same time, the mesoporous carbon nitride has abundant defective pyridinic N and pyrrolic N vacant sites, which can provide additional Li adsorption sites, and the defective pyridinic N has stronger electronegativity and can more easily adsorb Li, thereby significantly improving the electrochemical performance of lithium-ion batteries when it is used as a negative electrode material.
[0120] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing mesoporous carbon nitride used as a negative electrode material for lithium ion batteries, characterized in that: The preparation method comprises the following steps: (1) mixing carbon and nitrogen compounds, chlorides and water, and fully dissolving them to obtain a precursor solution; (2) freeze-drying the precursor solution obtained in step (1) to obtain a precursor powder; (3) subjecting the precursor powder obtained in step (2) to a high temperature treatment in at least two heating stages to obtain a crude carbon nitride product; (4) sequentially acid-washing, water-washing and drying the crude carbon nitride obtained in step (3) to obtain mesoporous carbon nitride; The carbon-nitrogen compound in step (1) comprises any one of urea, dicyandiamide or melamine, or a combination of at least two thereof; The chloride in step (1) comprises potassium chloride and / or sodium chloride; The mixing mass ratio of the carbonitride and the chloride in step (1) is (5-15):1; The freeze-drying process in step (2) includes low-temperature freezing and vacuum sublimation performed sequentially; The high temperature treatment in step (3) includes two heating stages, namely the first heating stage and the second heating stage; the heating rate of the first heating stage is 4-6°C / min, the target temperature of the first heating stage is 300-400°C, and the insulation time of the first heating stage is 2-4h; the heating rate of the second heating stage is 1-3°C / min, the target temperature of the second heating stage is 600-650°C, and the insulation time of the second heating stage is 3-5h.
2. The preparation method according to claim 1, characterized in that: The carbon-nitrogen compound in step (1) is urea.
3. The preparation method according to claim 1, characterized in that: The chloride in step (1) is potassium chloride.
4. The preparation method according to claim 1, characterized in that: The mixing mass ratio of the carbon nitrogen compound and the chloride in step (1) is (8-12):
1.
5. The preparation method according to claim 1, characterized in that: The dissolution process in step (1) is also accompanied by stirring, and the stirring rate is 100-1000 rpm.
6. The preparation method according to claim 1, characterized in that: The low temperature freezing temperature is -10 to -50°C.
7. The preparation method according to claim 1, characterized in that: The absolute pressure of the vacuum sublimation is 1-10Pa.
8. The preparation method according to claim 1, characterized in that: The acid solution used for pickling in step (4) includes any one of hydrochloric acid solution, nitric acid solution or sulfuric acid solution.
9. The preparation method according to claim 8, characterized in that: The acid solution used for pickling in step (4) is hydrochloric acid solution.
10. The preparation method according to claim 1, characterized in that: The acid concentration used in the pickling in step (4) is 0.08-0.12 mol / L.
11. The preparation method according to claim 1, characterized in that: The washing in step (4) is carried out using deionized water.
12. The preparation method according to claim 1, characterized in that: The water washing in step (4) is carried out until the washing liquid is neutral.
13. The preparation method according to claim 1, characterized in that: The drying temperature in step (4) is 80-120°C.
14. The preparation method according to claim 1, characterized in that: The drying time in step (4) is 4-6 hours.
15. The preparation method according to claim 1, characterized in that: The preparation method comprises the following steps: (1) mixing urea, potassium chloride and water, wherein the mass ratio of urea to potassium chloride is (8-12):1, and stirring at a rate of 100-1000 rpm until the urea is fully dissolved to obtain a precursor solution; (2) freeze-drying the precursor solution obtained in step (1) to obtain a precursor powder; the freeze-drying process includes low-temperature freezing and vacuum sublimation performed in sequence, and the low-temperature freezing temperature is -10 to -50°C, and the absolute pressure of the vacuum sublimation is 1-10Pa; (3) subjecting the precursor powder obtained in step (2) to high temperature treatment to obtain a crude carbon nitride product; the high temperature treatment comprises two heating stages, namely a first heating stage and a second heating stage; the heating rate of the first heating stage is 4-6°C / min, the target temperature is 300-400°C, and the holding time is 2-4h; the heating rate of the second heating stage is 1-3°C / min, the target temperature is 600-650°C, and the holding time is 3-5h; (4) The crude carbon nitride obtained in step (3) is acid-washed, water-washed and dried in sequence to obtain mesoporous carbon nitride; the acid-washing is performed using a hydrochloric acid solution with a concentration of 0.08-0.12 mol / L; the water-washing is performed using deionized water until the washing solution is neutral; the drying temperature is 80-120° C. and the drying time is 4-6 h.
16. A mesoporous carbon nitride used as a negative electrode material for a lithium ion battery obtained by the preparation method according to any one of claims 1 to 15, characterized in that: The average pore diameter of the mesoporous carbon nitride is 3-6 nm.
Citation Information
Patent Citations
Method for preparation of water-soluble luminous graphite-phase carbon nitride nano kelp
CN105152147A
Preparation method of ionized carbon nitride
CN112142023A